2006
DOI: 10.1007/s00417-006-0377-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uncomplicated phacoemulsification on the central retina in diabetic and non-diabetic subjects

Abstract: Foveal thickness and foveal volume demonstrate a subclinical increase within 4 weeks after uncomplicated cataract surgery in up to 1/3 of the patients. The amount and frequency of early postoperative subclinical retinal thickening was higher than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 32 publications
3
47
1
1
Order By: Relevance
“…Biro and colleagues (2008) found no differences between the preoperative and postoperative day 1 foveal and perifoveal retinal thickness. However, increases were found in the perifoveal 3.0 and 6.0 mm diameter and foveal area thickness on postoperative days 7, 30, and 60 (Degenring et al 2007). No signifi cant differences in foveal thicknesses were detected in other studies in week 1 (Cheng et al 2002;Degenring et al 2007).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Biro and colleagues (2008) found no differences between the preoperative and postoperative day 1 foveal and perifoveal retinal thickness. However, increases were found in the perifoveal 3.0 and 6.0 mm diameter and foveal area thickness on postoperative days 7, 30, and 60 (Degenring et al 2007). No signifi cant differences in foveal thicknesses were detected in other studies in week 1 (Cheng et al 2002;Degenring et al 2007).…”
Section: Discussionmentioning
confidence: 53%
“…However, increases were found in the perifoveal 3.0 and 6.0 mm diameter and foveal area thickness on postoperative days 7, 30, and 60 (Degenring et al 2007). No signifi cant differences in foveal thicknesses were detected in other studies in week 1 (Cheng et al 2002;Degenring et al 2007). Cheng and colleagues (2002) observed no increases in mean foveal thickness in week 1 in 80 patients.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Degenring ve ark. [8] DM olan ve olmayan hastalarda komplike olmayan standart katarakt ameliyatından sonraki birinci ve dör-düncü haftada maküla değişikliklerini OKT ile incelediklerinde; ameliyat sonrası maküla kalınlığı ve maküla hacminde subklinik bir artış olduğunu ve bu artışın diyabetli hasta grubunda istatistiksel olarak anlamlı olduğunu ve buna paralel olarak da dördüncü haftada görme keskinliğinin bu grupta diyabeti olmayan gruba göre daha düşük olduğunu gözlemlemişlerdir.…”
Section: Discussionunclassified
“…[65][66][67] the pathogenesis of these complications may be related to the changes and rise in the concentration of VEGF in response to surgical trauma and inflammation. 29 one study investigated cmE following cataract surgery in patients with diabetic retinopathy and they reported that 6 % of the controls and 12 % of diabetic eyes developed a clinical cmE up to 6…”
Section: Prophylactic Intravitreal Bevacizumab For Diabetic Macular Omentioning
confidence: 99%